Microbial biomass, microbial activity, and carbon pools under different land-use systems in the Brazilian cerrados - Renz, TE; Neufeldt, Henry; Ayarza, Miguel Angel; Resck, DVS; Zech, W. (International Center for Tropical Agriculture, 1999)
In the Brazilian savannas, or Cerrados the rapid advance in agriculture and cattle ranching is affecting soils through, for example, accelerated erosion and depletion of soil organic matter (SOM). Changes in soil microbial biomass are good indicators of changes in SOM. We therefore assessed the effects of agricultural and pastoral use of a clayey Oxisol in the Cerrados on soil microbial biomass, and evaluated the usefulness of this parameter in studying SOM dynamics in savanna ecosystems. Surface soil horizons under a pine forest and different crop and pasture treatments were compared with the control soil under native savanna. Soil microbial carbon (C mic), potential microbial activity, pH, organic C, water-extractable organic carbon (WEOC), and total N were assessed for the different systems. Compared with native savanna, crop cultivation and reforestation depleted C mic. The C mic,/C quotients indicated that C might continue to decline in these two systems. Changing from conventional to no tillage appears to slow down the depletion of topsoil C mic, C, and other parameters measured. Pasture establishment in native savanna did not clearly change C mic, but stimulated microbial activity. The ratio of microbial activity to Cmic was higher under pastures than under the other systems. Soil microbial carbon was shown to be closely related to the soil carbon cycle. Water-extractable organic carbon, possibly the most important source of C for microbes, consists of root exudates and litter degradation products. Root density, together with organic matter (OM) input and soil cover, was therefore assumed to be a major factor controlling the amount of C mic. Microbial growth was hypothesized to be C-limited in the crop systems and possibly N-limited in the pastures. The results indicate that the C mic/C ratio can be used as an indicator of OM dynamics in highly weathered tropical soils.